Amino Acid Profiling and SDS-PAGE Analysis of Protein Isolates Obtained from Nonconventional Sources - Muhammad Sibt-e-Abbas; Masood Sadiq Butt; Mian N. Riaz; Tadesse Fikre Teferra; Iahtisham Ul-Haq (Journal of Food Quality)
Proteins play an imperative role in enhancing the nutritional status of the human body. The present study was designed to determine the molecular weight of protein isolates prepared from defatted oilseeds, i.e., sesame, flaxseed, and canola, using SDS-PAGE. The electropherogram revealed protein bands ranging from 15 to 65 kDa. Furthermore, proteins were subjected to amino acid profiling followed by calculation of amino acid score with reference to requirement for preschool children. The amino acid profiling results indicated that sesame protein isolates (SPI) exhibited the highest values for aromatic amino acids, histidine, isoleucine, and valine. However, the maximum values for sulfur-containing amino acids were depicted by flaxseed protein isolates (FPI). Moreover, the lysine content was highest in canola protein isolates (CPI). Results indicated better profile and quality of proteins, capable to meet the requirements of essential amino acids, especially for preschoolers. Moreover, the values for the protein digestibility corrected amino acid score (PDCAAS) and in vitro protein digestibility (IVPD) were also determined. Conclusively, protein isolates from defatted oilseeds exhibit better-quality proteins with a balanced amino acid profile. By potential utilization in numerous food products, these proteins can play a pivotal role in fulfilling the nutritional requirements of individuals, especially in developing economies.